Transformation of Sulfonamides and Tetracyclines during Anaerobic Fermentation of Liquid Manure. Issue 1 (1st January 2017) - Spielmeyer, Astrid; Stahl, Franziska; Petri, Madeleine S.; Zerr, Walter; Brunn, Hubertus; Hamscher, Gerd
Abstract : Liquid manure is frequently used as soil fertilizer due to its high nutrient content. It can also contain residues of pharmaceuticals, such as antibiotics, if farm animals are medicated. The anaerobic fermentation process in biogas plants is discussed as one way to reduce the input of antibiotics into the environment. Therefore, 10 worldwide‐applied sulfonamides (sulfachloropyridazine, sulfadiazine, sulfadimethoxine, sulfaguanidine, sulfamerazine, sulfamethazine, sulfamethoxazole, sulfamethoxypyridazine, sulfapyridine, and sulfathiazole) and four frequently used tetracyclines (chlortetracycline, doxycycline, oxytetracycline, and tetracycline) were investigated concerning their elimination pattern during anaerobic fermentation. Batch fermenters with autoclaved and non‐autoclaved inoculum were utilized to distinguish between biotic and abiotic elimination pathways. Overall, sulfadimethoxine, sulfamethoxypyridazine, and sulfamethoxazole showed the highest elimination, which was considerably reduced by autoclaving before inoculation. Structure elucidation via nuclear magnetic resonance and different mass spectrometry techniques revealed only minor structural modifications such as O‐demethylation and hydrogenation, which did not result in a considerably reduced antimicrobial activity. These results show that, especially, sulfonamides are more persistent than expected. Future studies should deal with the elucidation of relevant process parameters for an enhanced compound degradation. Core Ideas: Veterinary antibiotics were incubated in both active and autoclaved inoculum. Substance‐related elimination profiles were found for sulfonamides and tetracyclines. Autoclaving of the inoculum reduced the elimination of the sulfonamides. O‐Demethylation and hydrogenation led to various transformation products. Some transformation products showed a reduced antimicrobial activity.